Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Evaluate $$(\frac{1}{-\sqrt{2}+\sqrt{2}i})^{2011}$$

So ...

$$(\frac{1}{-\sqrt{2}+\sqrt{2}i})^{2011} = (-\sqrt{2}+\sqrt{2}i)^{-2011}$$

$$\theta=\pi - \arctan(\frac{\sqrt{2}}{\sqrt{2}}) = \frac{3\pi}{4}$$

$$-\sqrt{2}+\sqrt{2}i=\cos{\theta} + i \sin{\theta}$$

$$(-\sqrt{2}+\sqrt{2}i)^{-2011} =\cos{(-2011\theta)} + i \sin{(-2011\theta)} = e^{i(-2011)\theta}$$

Is it correct?

The given answer is


$$\arg{z} = \frac{3\pi}{4}, \qquad z=2e^{i \frac{3\pi}{4}}$$

$$LHS = (\frac{1}{z})^{2011}=2^{-2011}e^{-2011(\frac{3\pi}{4})i} = 2^{-2011} e^{-(\color{red}{1508\pi i} + \frac{\pi i }{4})} = 2^{-2011}e^{-\frac {\pi i}{4}} = 2^{-2011} \color{blue}{\frac{1 - i}{\sqrt{2}}} = ... $$

Why is the red $1508\pi i$ removed in the following step?

How do I get the blue $\frac{1 - i}{\sqrt{2}}$ from the prev step?

share|cite|improve this question
$\frac{1}{-\sqrt{2}+i\sqrt{2}}=\frac{-\sqrt{2}-i\sqrt{2}}{4}=\frac{1}{2}\left( -\frac{\sqrt{2}}{2}-i\frac{\sqrt{2}}{2} \right)$ This explains the term $2^{-2011}$, but the argument is $\frac{5}{4}\pi$. – Mark Apr 14 '12 at 6:22
How is it possible for $\cos\theta =-\sqrt{2}$ and $\sin\theta=\sqrt{2}$? You have to convert $z$ fully to polar form $re^{i\theta}$. Here the modulus $r$ is not $1$. – anon Apr 14 '12 at 6:31
Updated question fixing signs – Jiew Meng Apr 14 '12 at 8:05
up vote 2 down vote accepted

$$ \frac{1}{-\sqrt{2}+i\sqrt{2}}\frac{-\sqrt{2}-i\sqrt{2}}{-\sqrt{2}-i\sqrt{2}}=\frac{-\sqrt{2}-i\sqrt{2}}{4}=\frac12\frac{-1-i}{\sqrt{2}} $$ which has absolute value $\dfrac12$ and argument $\dfrac{5\pi}{4}$, so $\left(\frac{1}{-\sqrt{2}+i\sqrt{2}}\right)^{2011}$ has absolute value $1/2^{2011}$ and argument $\frac{5\pi}{4}\cdot2011\equiv-\frac{\pi}{4}\pmod{2\pi}$. Therefore, $$ \left(\frac{1}{-\sqrt{2}+i\sqrt{2}}\right)^{2011}=\frac{1}{2^{2011}}\frac{1-i}{\sqrt{2}} $$ If, as the title suggests, the exponent is $-2011$, we simply need to take the reciprocal: $$ \left(\frac{1}{-\sqrt{2}+i\sqrt{2}}\right)^{-2011}=2^{2011}\frac{1+i}{\sqrt{2}} $$

share|cite|improve this answer
Updated my question, fixing the signs. Anyways, how do I get from $2^{-2011}e^{-\frac {\pi i}{4}}$ to $2^{-2011} \frac{1 - i}{\sqrt{2}}$ – Jiew Meng Apr 14 '12 at 8:15
Oh I simply "reverse" the polar form? – Jiew Meng Apr 14 '12 at 8:18
Yes, polar and cartesian form: $$ e^{-\frac{\pi i}{4}}=\frac{1-i}{\sqrt{2}} $$ – robjohn Apr 14 '12 at 12:35

Ok, lots of bits here and there.

With respect to your answer, it is not true that $-\sqrt{2}+\sqrt{2}i=\cos{\theta} + i \sin{\theta}$, as in particular the length of the element on the left is $2$ and the length of the element on the right is $1$.

With respect to your question about the red bit, recall that $e^{2 i \pi} = 1$. So one can simply ignore the part of the exponent properly divisible by 2.

Similarly, they get the blue part by simply evaluating $e^{-i\pi/4 }$.

share|cite|improve this answer

First off, let's get the signs correct:


Second, if $z=-\sqrt{2}+\sqrt{2}i=\sqrt{2}(-1+i)$, then we do have a magnitude of two:

$$|z|=\sqrt{2}\cdot |-1+i|=\sqrt{2}\cdot\sqrt{(-1)^2+1}=2.$$

The angle $\theta=\frac{3}{4}\pi$ of $z$ is correct so finally

$$z^{-2011}=(2e^{\frac{3}{4}\pi i})^{-2011}=2^{-2011}\exp\left(-\frac{6033}{4}\pi i\right)=2^{2011}e^{-\pi i/4}$$

because $6033\equiv1\bmod8$. We could also evaluate $e^{-\pi i/4}$ as $(1-i)/\sqrt{2}$ and get $2^{-(2011+1/2)}(1-i)$.

share|cite|improve this answer

Since everyone has been answering about the blue part, I will answer about the red part:

\begin{eqnarray*} 2^{-2011} e^{-(\color{red}{1508\pi i} + \frac{\pi i }{4})} &=& 2^{-2011}e^{-(\color{red}{1508\pi i})} \cdot e^{\left( \frac{\pi i }{4}\right)} \\ &=& 2^{-2011}{\left(e^{(\color{red}{2\pi i})}\right)}^{-\frac{1508}{2}} \cdot e^{\left( \frac{\pi i }{4}\right)} \\ &=& 2^{-2011}{(\color{red}{1})}^{-\frac{1508}{2}} \cdot e^{\left( \frac{\pi i }{4}\right)} \hspace{5mm} \text{(Using the fact that $e^{2 \pi i } = 1$)} \\ &=& 2^{-2011} e^{\left( \frac{\pi i }{4}\right)}. \end{eqnarray*}

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.